Case Report: Capitalizing on Development and Activity-Dependent Plasticity, an Interaction With Pediatric-Onset Spinal Cord Injury - Goode-Roberts, MacKenzie; Noonan, Kathryn; Stout, Danielle; Calvery, Margaret; Brothers, Kyle; Doonan, Nicole Williams; Behrman, Andrea L. (Frontiers in Pediatrics, 2022)
Background: Spinal cord injury (SCI) in infancy halts typical development secondary to paralysis/paresis and the limited ability to engage with the environment. Traditional therapies further restrict a child via bracing, equipment, and medications. In contrast, activity-based restorative therapies (ABRT) promote activation of the neuromuscular system below the level of injury and affords a more typical sensorimotor experience. Case description: A premature male infant exhibiting hypotonia, poor head control, and extremity weakness was diagnosed at age 5 months with a remote incomplete upper cervical SCI based on magnetic resonance imaging (MRI), presumed to have occurred perinatally. A premature infant, exhibiting hypotonia and cleared neurologically for genetic or brain abnormalities, was at 5 months diagnosed with a C2-C3 SCI occurring either in utero or at birth. From 4-15 months of age, he received physical, occupational and speech therapies. Enrolled in an ABRT program at 15 months, he was unable to sit, pull-to-stand, stand, or walk and with had upper extremity impairments. Results of the The Bayley-III Scales of Infant and Toddler Development revealed gross and fine motor scores consistent with a 4-month-old. Methods: ABRT was provided 5 day/week: 1.5 hours of activity-based locomotor training and 1 hour of activity-based occupational therapy. Results: ABRT is reported for 177 sessions and is on-going. Improvements are noted in trunk control, standing, walking, grasp, in-hand manipulation, and associated kinematics. Bayley-III fine motor score improved to that of a 16-month-old and gross motor score to that of a 7-month-old. Discussion: While the two treatment periods (i.e., 4-15 months old and 15-24 months) were each ~ 9 months, the child’s accelerated progress toward typical development during the latter, ABRT period is noteworthy. In comparison to the period of traditional therapies in which paralysis was compounded by a restrictive environment and compensation, ABRT provided a potentially rich sensorimotor experience with an emphasis on active weight-bearing and proper kinematics to activate the neuromuscular system below the lesion in an age-appropriate, task-specific context of activities. Improved physical capacity enabled exploration more typically associated with development at this age expanding the positive impact to other developmental domains.